If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 9 + 6x + 3 = 0 Reorder the terms: 9 + 3 + 5x + 6x = 0 Combine like terms: 9 + 3 = 12 12 + 5x + 6x = 0 Combine like terms: 5x + 6x = 11x 12 + 11x = 0 Solving 12 + 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 11x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 11x = 0 + -12 11x = 0 + -12 Combine like terms: 0 + -12 = -12 11x = -12 Divide each side by '11'. x = -1.090909091 Simplifying x = -1.090909091
| 6/6x=89x/1 | | 3x+5+4x+7=19 | | 6*6x=89x*1 | | -9d+7-6d=-133 | | 2b^2+4b+2=0 | | 3x+2-x=6+5x-3 | | m-1/3=-9 | | 2*5x=5x*6 | | 6x+6+7x+5=115 | | 3*x=7*1x | | 6x+6+8x+7=69 | | -2=-49x(2)-7x | | 4a^2-147=0 | | -2g^2-6g+14x^2/(g+5) | | 4x+4+2x+9=31 | | -2g^2-6g+14x^2/g+5 | | 12x+16=3x+9 | | 28x^5-36x^4+8x^3= | | 7x*6=34x*6 | | 5x+2+2x+3=47 | | X/7+10=9 | | 1/2n+10=20 | | 2x-9=-33-4x | | 34x*6=7x*6 | | 2x+0.625=3x-0.625 | | X/3+5=-1 | | 3x-6=-1 | | 6x*6=7*4x | | 3x*5=7x*6 | | f(x)=4x^3+5x^2-6x-4 | | -15b^2+102b+21= | | 35=-4+5(a+3) |